Preparation and Structural Characterization of Dy3+-Doped PBiNaGd Glass. Issue 1 (12th February 2021) - Rajagukguk, Juniastel; Rahmaniar; Harahap, Nursaida; Situmorang, Rappel; Panggabean, Deo D.; Kaewkhao, Jakrapong
Abstract: The Dy:PBiNaGd glasses were made from chemical compounds with a composition (70-x)P2 O5 -10Bi2 O3 -10Na2 O-10Gd2 O3 which were doped by active xDy2 O3 ion (where x  = 0; 0.05; 0.1; 0.5; 1.0; 3.0 (mol%). All of proposed compositions are in the powder form with a mass of 20 gram of mixture in an alumina crucible and prepared by the melt-quenching method. The glasses those have been obtained with a size (3 × 10 × 10) mm 3 and smoothed to get a flat surface and high transparency. The physical properties including of density, molar volume, refractive index, ion concentration, molar refractivity, and susceptibility of the glasses medium have been obtained and analyzed. This amorphous nature is confirmed by x-ray diffraction instrument (XRD). Based on the XRD ovservation found that the Dy:PBiNaGd glasses are amorphous. Measurement of FTIR spectra for Dy:PBiNaGd glass shows that the asymmetry strain in the P-O-P (POP) bond appear at an area of 861 cm −1 absorptions.